LINC00173 Interacts With DNMT1 to Regulate LINC00173 Expression via Promoter Methylation in Hydroquinone-Induced Malignantly Transformed TK6 Cells and Benzene-Exposed Workers. (4th February 2022) - Zhang, Haiqiao; Pan, Zhijie; Ling, Xiaoxuan; Tan, Qiang; Yuan, Qian; Qin, Jiheng; Zhong, Bohuan; Li, Huifang; Chen, Jialong; Zhang, He; Chen, Xiaowen; Shi, Zhizhen; et al.
Abstract: Long-term exposure to benzene or its metabolite, hydroquinone (HQ), can causally contribute to acute myeloid leukemia. Long-noncoding RNAs are essential epigenetic regulators with critical roles in tumor initiation and malignant progression; however, the mechanism by which aberrantly expressed LINC00173 (long intergenic nonprotein coding RNA 173) regulates the pathogenesis of acute myeloid leukemia is not fully understood. Here, we found that the expression of LINC00173 decreased while the expression of DNA methyltransferase 1 (DNMT1) increased, and the methylation of LINC00173 promoter was negatively correlated with LINC00173 expression in GEPIA, CCLE databases, benzene-exposed workers, B-cell non-Hodgkin's lymphoma, K562, U937, or HQ-induced malignantly transformed TK6 (HQ-MT cells). Furthermore, in 5-aza-2'-deoxycytidine (DNA methyltransferase inhibitor) or trichostatin A (histone deacetylation inhibitor)-treated HQ-MT cells, the expression of LINC00173 was restored by reduced DNA promoter methylation levels. HQ-MT cells with DNMT1 knockout by CRISPR/Cas9 restored the expression of LINC00173 and inhibited the DNA methylation of its promoter as well as enrichment of DNMT1 to promoter. Overexpression of LINC00173 inhibited the expression of DNMT1, cell proliferation, tumor growth, enhanced chemosensitivity to cisplatin, and apoptosis in HQ-MT cells. LINC00173 interacts with DNMT1 to regulate the methylation of LINC00173 promoter. Overall, this study provides evidence that interaction between DNMT1 and LINC00173 regulates the expression of LINC00173 by regulating its promoter methylation level, thus regulating the function of HQ-MT cells in vitro and in vivo, providing a new therapeutic target for benzene-induced tumor.